Big Data Analytics for Business Management: Driving Innovation and Competitive Advantage - Sridharlakshmi, Narayana Reddy Bommu; Karanam, Raghunath Kashyap; Boinapalli, Narasimha Rao; Allam, Abhishekar Reddy; Rodriguez, Marcus (Asian Business Review, 2024)
The study aims to investigate how Big Data Analytics may revolutionize modern business management by fostering innovation and providing a competitive edge. The study looks at the adoption rates, strategic implementation, and effects of Big Data Analytics on organizational performance indicators like revenue growth, customer acquisition, retention, and market share. It thoroughly evaluates the literature and case studies and analyzes future trends. The results highlight how businesses use BI tools, data visualization strategies, and advanced analytics capabilities to boost operational effectiveness and spur revenue growth. These developments highlight the growing use and strategic significance of big data analytics. However, to guarantee the appropriate and fair implementation of Big Data Analytics in company management practices, issues like data privacy and security concerns call for solid data governance frameworks and governmental interventions. The report offers insightful information and policy recommendations for businesses looking to use data-driven tactics to confidently and nimbly negotiate the challenges of the modern digital economy.
Keywords: Big Data; Competitive Advantage; Data-Driven Decision Making; Predictive Analytics; Business Intelligence; Data Mining; Strategic Management